07.09 Influence of b-cell activating factor genetic variants in sjögren's syndrome related atherosclerosis. (1st March 2017) - Karageorgas, Theofanis; Nezos, Adrianos; Ioakeimidis, Dimitrios; Koutsilieris, Michael; Mavragani, Clio P
Abstract : Background: Recent data highlight the increased risk for premature atherosclerosis in primary Sjogren's syndrome (pSS) patients. Given a potential role of B cells in atherosclerotic plaque formation, we explored the potential contribution of B-cell activating factor (BAFF) in pSS-related atherosclerosis. Materials and methods: 72 patients, fulfilling the ACR/EULAR criteria for pSS, with detailed clinical, laboratory and histopathological data regarding both pSS and traditional risk factors of atherosclerosis underwent carotid and femoral arteries Doppler ultrasound scan for detection of atherosclerotic plaque. Additionally, the prevalence of 5 polymorphisms (rs1224141, rs12583006, rs61756766, rs9514828, rs1041569) in the BAFF gene was examined. BAFF mRNA levels were measured by real time PCR in a subgroup of 32 patients with available peripheral blood cDNA. Univariate and multivariate statistical analyses were performed. Results: In the subgroup of 32 pSS patients, BAFF mRNA levels were significantly higher in patients with plaque (17 out of 32 patients) compared to those without plaque (p=0.03). In the entire cohort of 72 pSS patients, the prevalence the T/T genotype of the rs9514828 polymorphism, which is known to reside in the promoter area of the BAFF gene, was significantly higher in pSS patients with plaque compared with those without plaque (35.6% vs 8.0%, p=0.031 respectively, OR: 6.4, CI: 1.3–30.6). The multivariate analysis also showed the rs9514828 BAFF polymorphism to be independently associated with the presence of plaque after adjustment for age, hypertension, smoking and dyslipidemia (OR=3.5, CI: 1.2–10.1). Conclusions: In pSS patients the presence of atherosclerotic plaque was significantly associated both with increased BAFF mRNA levels and the T/T genotype of rs9514828 BAFF polymorphism implying a potential role of BAFF in the pathogenesis of pSS-related atherosclerosis. Further studies are warranted in order to elucidate this association. Grants/acknowledgements: Dr. T.Karageorgas' work was supported by a State Scholarship Foundation (IKY) Fellowship of Excellence for Postgraduate Studies in Greece-Siemens Programme.